Pengaruh Kerjasama Tim, Kemampuan Kerja, dan Pengalaman Kerja Terhadap Kinerja Karyawan CV Indoprinting Kota Semarang: The Effect Of Teamwork, Work Ability, And Work Experience On Employee Performance CV Indoprinting Semarang City - Nuha, Muhammad; Amalia Krisna Dewi (Universitas Bojonegoro, 2024)
Human resources (HR) or workforce or an employee is the main asset in a company. In order to show the performance of employees in CV Indoprinting Semarang City Branch, the company needs to look at it from various sides, one of which is seen from the cooperation team, Work Ability, and Work Experience of employees. The purpose of this study was to determine and analyze whether there is an influence of the Cooperation Team, Work Ability, and Work Experience on Employee Performance of CV Indoprinting Semarang City Branch. This study uses a quantitative method with primary data (questionnaire). The population in this study was 42 employees and the sample used in this study was a saturated technique sample which means the number is the same as the population. The data analysis technique used multiple linear regression. The Independent Variables in this study are Team Cooperation (X1), Work Ability (X2), and Work Experience (X3) and Employee Performance as the Dependent Variable (Y). The results of this study indicate that simultaneously the variables of Team Cooperation, Work Ability, and Work Experience together have a positive and significant effect on Employee Performance of CV Indoprinting Semarang City Branch. The coefficient of determination (R Square) value is 0.565. This means that 56.5% of Employee Performance can be explained by the variables of Teamwork, Work Ability, and Work Experience. While 43.5% can be explained by other variables not used in this study